PENINGKATAN KAPABILITAS PEJABAT PENATAUSAHAAN KEUANGAN DAN BENDAHARA DALAM PENATAUSAHAAN PERTANGGUNGJAWABAN KEUANGAN TRANSAKSI NON TUNAI - Aini Indrijawati; Mediaty; Muhammad Achyar Ibrahim; Abdul Rahman; Rosnawintang (LP2M Universitas Hasanuddin, 2020)
Abstract. The application of non-cash transactions aims to provide flexibility and convenience to Treasurers and recipients of services in the implementation of non-cash payment transactions while ensuring transparent and accountability elements, while Commitment Making Officers (PPK) can be used as controls so that non-cash transactions can be referred , is verified and analyzed which will have an impact on the issuance of SPM, and is used to prepare financial reports and audit purposes. The purpose of the implementation of community service activities is to increase the capability of financial administration officials so that the realization of accountability and transparency in financial management, this can only be achieved if various supporting factors have been fulfilled such as the preparation of regulations and policies, preparation of competent human resources and integrated information systems that are adequate. Community service activities are carried out using lecture and tutorial methods. The reality on the ground shows that the problem that arises in overcoming government regulations regarding non-cash transactions is the lack of understanding of the staff of the Bone district government finance regarding the rules relating to the management of non-cash cash. The results of this activity indicate an increase in the capability of the treasurer of expenditure to manage non-cash transactions properly, this is evident in the documents used in the implementation of non-cash transactions that are complete and able to show elements of transparency and accountability. Keywords: Non-cash transactions, administration, accountability. Abstrak. Penerapan transaksi non-tunai bertujuan agar dapat memberikan fleksibilitas dan kemudahan kepada Bendahara dan penerima jasa dalam pelaksanaan transaksi pembayaran non-tunai dengan tetap menjamin unsur transparan dan akuntabilitas, sedangkan bagi Pejabat Pembuat Komitmen (PPK) dapat dijadikan kontrol sehingga transaksi non-tunai dapat dirujuk, diverfikasi dan dianalisis yang akan berdampak di terbitkannya SPM, serta digunakan untuk pembuatan laporan keuangan dan kepentingan pemeriksaan. Tujuan dari pelaksanaan kegiatan pengabdian adalah untuk meningkatkan kapabilitas pejabat penatausahaan keuangan agar terwujudnya akuntabilitas dan transparasi pengelolaan keuangan, ini hanya dapat dicapai apabila berbagai faktor pendukung sudah terpenuhi seperti penyiapan regulasi dan kebijakan, penyiapan SDM yang berkompeten serta sistem informasi yang terintegrasi sudah memadai. Kegiatan pengabdian dilaksanakan dengan menggunakan metode ceramah dan tutorial. Kenyataan di lapangan menunjukkan bahwa permasalahan yang muncul dalam mengatasi peraturan pemerintah tentang transaksi non-tunai adalah kurangnya pemahaman staf bagian keuangan pemerintah kabupaten Bone tentang aturan-aturan yang berkaitan dengan pengelolaan kas non tunai. Hasil kegiatan ini menunjukkan adanya peningkatan kapabilitas bendahara pengeluaran untuk mengelola transaksi non tunai dengan baik, hal ini nampak pada dokumen-dokumen yang digunakan dalam pelaksanaan transaksi non tunai telah lengkap dan mampu menunjukkan unsur transparan dan akuntabilitas. Kata Kunci: Transaksi non tunai, penatausahaan, pertanggungjawaban keuangan